2020
DOI: 10.3389/fbioe.2020.524676
|View full text |Cite
|
Sign up to set email alerts
|

Design and Construction of Portable CRISPR-Cpf1-Mediated Genome Editing in Bacillus subtilis 168 Oriented Toward Multiple Utilities

Abstract: Bacillus subtilis is an important Gram-positive bacterium for industrial biotechnology, which has been widely used to produce diverse high-value added chemicals and industrially and pharmaceutically relevant proteins. Robust and versatile toolkits for genome editing in B. subtilis are highly demanding to design higher version chassis. Although the Streptococcus pyogenes ( Sp ) CRISPR-Cas9 has been extensively adapted for genome eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The general sgRNAs were designed based on a previous study ( 35 ) via online software ( http://chopchop.cbu.uib.no/ ) ( 36 ). The 3′-terminal extended sgRNAs for the target region (N20) were designed by gradually adding the corresponding base.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The general sgRNAs were designed based on a previous study ( 35 ) via online software ( http://chopchop.cbu.uib.no/ ) ( 36 ). The 3′-terminal extended sgRNAs for the target region (N20) were designed by gradually adding the corresponding base.…”
Section: Methodsmentioning
confidence: 99%
“…To construct a multiplex base editing system for the modification of the SecYEG complex, plasmid pAD123 ( 35 ) was used as the donor vector for the expression of sgRNA driven by a strong constitutive promoter P veg . Using the pAD123, the plasmids pAD-T0, pAD-T3, pAD-secE, and pAD-secG that harboured sgRNAs targeting secY (T0), secY (T3), secE (ET) and secG (GT), respectively, were generated by reverse PCR using primers secYT0-F/secYT0-R, secYT3-F/secYT3-R, secEET-F/secEET-R and secGGT-F/secGGT-R, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that a chromosomally integrated Cas12a was able to facilitate large cluster deletion in B. subtilis by use of only one sgRNA. 18 Here, we demonstrated highly efficient Cas9-mediated large cluster deletion by using a one plasmid system with only one sgRNA, which has to be chosen carefully within the targeted sequence. In addition to the distance between cut site and homologous flanks, accessibility of the targeted region as well as the three-dimensional structure of the genome might also need to be considered especially when aiming for large genomic region deletions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above technologies, B. subtilis gene-editing technology have been further developed based on CRISPR-Cas9 technology. Hao et al (2020) design a CRISPR-Cpf1-based toolkit employing a type V Cas protein, Cpf1 from F. novicida . Using this platform, they precisely delete single gene and gene cluster in B. subtilis with high editing efficiency, such as sacA, ganA, ligD,ligV , and bac operon.…”
Section: Crispr-cas9 System Application For B Subtilismentioning
confidence: 99%